Empirical Facts of Educational Chances for Women in Islamic World: Past and Present - Handoko Ja'far; Taufik Rigo (Walisongo: Jurnal Penelitian Sosial Keagamaan, 2017)
This article explores educational opportunities in the early period of Islam until the 13th century, which shows the significant role of women in education. It can be argued that the role of women in education can be traced not only in certain areas of religious knowledge but also in the patronage of education and even in determining the political policy of the government. Unfortunately, compared to the next period until the 21st century, policy concerning education has recently turned to unfair treatment such as marginalization, exclusion, and even deprivation. What is surprising is that the reasons for the genitals, which deprive women of their right to participate in education, casually occurred. In other cases, socio-cultures are restricting their access to education. The factual errors on educational thoughts for women here are explicitly used as an empirical description in this study, while its purpose is to demonstrate the shift in the treatment of female education. The result expected in this study is to reach the historical footprint of Islamic education and ensure inappropriate reasons, such as genital terms, used and abused as arguments for not allowing women to get an education.